PERAN GURU DALAM MEMBENTUK KARAKTER SISWA KELAS III DI MI BUSTANUL ULUM KOTA BATU - Uswatun Hasanah; Rosichin Mansur; Lia Nur Atiqoh Bela Dina (JPMI: Jurnal Pendidikan Madrasah Ibtidaiyah, 2020)
Character is the nature, character, character, behavior of someone who can distinguish from others. If an educated person does not have good character, that person is the same as an uneducated person. Therefore, to instill character values in children is expected from an early age. In forming the character of students the role of the professional teacher is needed, where the teacher is not as an educator but also as a guide in order to guide students to have good character. So in this study will summarize the role of the teacher in shaping the character of students This research was conducted at MI Bustanul Ulum Kota Batu especially in class III. The purpose of this study is to describe the character of class III students, the role of the teacher in shaping character, supporting factors and inhibiting the role of the teacher in shaping. This type of research uses a qualitative research approach with the type of case study. Data collection uses observation, interviews, and documentation. Data analysis uses data reduction, data presentation, drawing conclusions. The results of this study are diverse student characters but are still interpreted positively, and the teacher's role as educator, instructor and trainer.